Primary squamous cell carcinoma of the thyroid gland successfully treated with surgical resection and adjuvant chemoradiotherapy. Issue 3 (1st March 2021) - Chu, Michael M H; Mirza, Omar; Bishop, Paul William; Pothula, Vijay
Abstract : A 57-year-old woman presented with a 3-month history of an enlarging thyroid mass causing breathlessness and dysphagia. Cross-sectional imaging showed a thyroid tumour infiltrating the trachea and abutting the oesophagus. She underwent panendoscopy, total thyroidectomy and planned tracheal resection, but due to intraoperative findings, a staged procedure was planned instead. Histological analysis revealed a poorly differentiated squamous cell carcinoma (SCC) which was positive on paired box gene 8 (PAX8) immunostaining, suggesting a diagnosis of primary thyroid SCC. She subsequently underwent total laryngectomy and bilateral neck dissections followed by radiotherapy with concurrent cisplatin chemotherapy. The patient remains disease-free 22 months after treatment. Median overall survival is 10 months for macroscopically completely resected tumours. PAX8 immunostaining is a novel technique which helps with the diagnostic challenge of distinguishing between primary thyroid SCC and SCC metastatic to the thyroid from extrathyroidal sites. Complete surgical resection with adjuvant chemoradiotherapy may result in a favourable outcome despite conflicting reports in the literature.